Comparison of linear and angular changes assessed in digital dental models and cone‐beam computed tomography. (14th November 2019) - Massaro, Camila; Losada, Carolina; Cevidanes, Lucia; Yatabe, Marilia; Garib, Daniela; Lauris, José Roberto Pereira; Ioshida, Marcos; Rey, Diego; Alvarez, Maria Antonia; Benavides, Erika; Rios, Hector; Aristizabal, Juan Fernando; et al.
Abstract: Objective: To compare the three‐dimensional (3D) linear displacements and the mesiodistal and buccolingual angulation changes after orthodontic treatment in digital dental models (DDMs) and 3D models derived from cone‐beam computed tomography (CBCT). Settings and Sample Population: Digital dental model and CBCT scans were selected from 24 adults who had undergone orthodontic treatment for mandibular anterior crowding. Material and Methods: 3D linear displacements and changes in angular measurements (mesiodistal and buccolingual angulation) were assessed in pre‐ and post‐treatment DDM and CBCT images using the software ITK‐snap and 3D SlicerCMF. Intra‐ and inter‐rater agreement of measurements in DDM and CBCT were tested using the intraclass correlation coefficient (ICC). DDM and CBCT measurements were compared using the Wilcoxon test ( P  < .05), ICC and Bland‐Altman plots. Results: Intra‐ and inter‐rater agreement varied from good (ICC > 0.75) to excellent (ICC > 0.90) for both DDM and CBCT measurements. Although no significant difference between DDM and CBCT methods was observed for linear measurements of tooth movement, the angular assessments were different for most measurements. The agreement between measurements from both assessments varied from poor to excellent. Conclusions: Longitudinal assessments of tooth movements including 3D linear displacements and mesiodistal and buccolingual angulation are reproducible when using both DDM and CBCT. Changes in angular measurements due to orthodontic treatment are discordant when measured in the digital models (clinical crown) and in the CBCT images (whole tooth).